Зв’язок стану щитоподібної залози з гормональним метаболічним статусом у постраждалих внаслідок аварії на ЧАЕС - Камінський, О. В. (Clinical Endocrinology and Endocrine Surgery, 2012)
Clinical data analysis for the first time resulted in identification of thyroid system status depending not only on the unfavorable factors of the Chernobyl NPP accident but on non-thyroid hormone values and body mass. The endogenous drivers had an extra stimulating impact on hyperplastic, hypertrophic and autoimmune process onset especially in the accident clean-up workers. Thyroid radiation effects are amplified due to the increased concentrations of insulin, leptin, cortisol, both with and leptin resistance and insulin resistance attributed to that.